EFEKTIFITAS TERAPI KOGNITIF PERILAKU TERHADAP KECEMASAN PADA PASIEN SKIZOFRENIA DI PUSKESMAS GABUS I PATI - Nita Fitria Widia Puspita Sari; Yeni Rusyani; Luluk Dermawan (PT. Hasba Edukasi Mandiri, 2025)
Anxiety is a condition characterized by excessive worry, accompanied by behavioral, emotional, and physiological reactions. One way to address anxiety in patients with schizophrenia is using cognitive behavioral therapy. Cognitive behavioral therapy is necessary in the management of schizophrenia patients because it can help them overcome anxiety responses caused by distorted negative thoughts. Cognitive therapy can provide clients with a foundation for thinking to express their negative feelings, understand their problems, and be able to overcome them and solve them. Objective: To analyze the effectiveness of cognitive behavioral therapy on anxiety in schizophrenia patients at Gabus I Pati Public Health Center. Research Methods: The research method used was an experimental one-group pre-test-post-test design. A sample of 36 respondents was selected using total sampling. Data analysis used the Wilcoxon test. Results: The Wilcoxon test showed a ρ value of 0.001, less than 0.05. Therefore, it can be concluded that cognitive behavioral therapy is effective for anxiety in schizophrenia patients at the Gabus I Community Health Center in Pati. Conclusion: The results of this study can be used by patients and families to manage anxiety in schizophrenia patients at home with the assistance of local health workers.